Ethics, morality and medical writing - Edgard NEHMÉ (International Arab Journal of Dentistry (IAJD), 2013)
“The purpose of all morality is to consider human life as apart that can win or lose and teach men the way to win.”For moral of ambiguity, Simone de Beauvoir